POTENSI PARIWISATA SYARIAH DALAM MEMBANGUN PEREKONOMIAN UMAT - Aulia, Syafa Hilyatul; Tsabithah, Hasna; supriyono, Supriyono (JURNAL DESTINASI PARIWISATA, 2023)
This study aims to see and analyze the potential of sharia tourism in Indonesia to develop the economy of the people (society), especially the Muslim community. This research was conducted using a descriptive qualitative method. Sources of data were obtained through various literature related to sharia tourism, both from previous journals, books, and news articles. Researchers look for relevant sources and then process and analyze these sources themselves to become a systematic thought or result. The main results of the study are that sharia tourism has great potential as part of the tourism industry in Indonesia, which is a large center for sharia tourism in the world because it has natural resources and human resources that support it, namely natural beauty, cultural diversity, and the world's largest Muslim population. , sharia tourism can contribute to improving the economy of the Muslim community (community) in particular and improving the country's economy in general. Keywords: sharia tourism, halal tourism, potential, develop the economy